Relaxant effect of thymol on smooth muscle - Aurora Pérez-Sánchez (Mexican Journal of Medical Research ICSA, 2023)
Thymol is a phenolic monoterpene with colorless crystalline shapes or white crystalline powder with a spicy, caucasian and sweet taste. Its chemical structure is characterized by a hydroxyl group (-OH) attached to a benzene ring. It provides for the hydroxylation of P-cymine along with its carvacrol’s isomer. In this molecule different therapeutic properties have been registered in this molecule, such as spasmolytic, anticancer, anti-inflammatory, fungicidal, antibacterial, antioxidant and hepatoprotective. This monoterpene is found in different species of the genus Thymus, especially T. Vulgaris and T. zigis with a percentage that fluctuates between 10% and 60% found in the aerial part of both plants, likewise, it is also found in Lagoecia cuminoides between a 73% and 95% and in Trachyspermum copticum between 37.2 and 72.3% in the seed and fruits of this plant. Studies on its beneficial effects on health have been carried out in different species, highlighting rats, mice, rabbits, guinea pigs, chickens, human cell lines; distinguishing human studies have been conducted 3 studies to decrease the effects of asthma, antitussive and anti-inflammatory effect on the lungs. The aim of this narrative article is to describe the processes of contraction and relaxation of smooth muscle and the spasmolytic effect of thymol in different smooth muscle tissues in rats, mice, guinea pigs and rabbits. Through this research, it is suggested to the scientific community to study the possible mechanisms of action of this molecule in the different types of smooth muscle tissue for subsequent clinical studies